Design and synthesis of new indole drug candidates to treat Alzheimer's disease and targeting neuro-inflammation using a multi-target-directed ligand (MTDL) strategy - Phoebe F. Lamie; Maha M. Abdel-Fattah; John N. Philoppes (Taylor & Francis Group, 2022)
A novel series of indole-based compounds was designed, synthesised, and evaluated as anti-Alzheimer's and anti-neuroinflammatory agents. The designed compounds were in vitro evaluated for their AChE and BuChE inhibitory activities. The obtained results revealed that compound 3c had higher selectivity for AChE than BuChE, while, 4a, 4b, and 4d showed selectivity for BuChE over AChE. Compounds 5b, 6b, 7c, and 10b exerted dual AChE/BuChE inhibitory activities at nanomolar range. Compounds 5b and 6b had the ability to inhibit the self-induced Aβ amyloid aggregation. Different anti-inflammatory mediators (NO, COX-2, IL-1β, and TNF-α) were assessed for compounds 5b and 6b. Cytotoxic effect of 5b and 6b against human neuroblastoma (SH-SY5Y) and normal hepatic (THLE2) cell lines was screened in vitro. Molecular docking study inside rhAChE and hBuChE active sites, drug-likeness, and ADMET prediction were performed.